Effect of Bacillus subtilis (Bacillus subtilis subsp.) inoculation on the fermentation characteristics of Penaeus sinensis by-products: Protease activity and volatile property. (1st March 2023) - Xu, Yan; Song, Ru; Jia, Zhe; Wei, Rongbian; Wang, Jiaxing; Sun, Jipeng
Abstract: Protease activity and volatile flavor compounds will determine the overall unique sensory of fermented products. In this study, the changes of protease activity of Penaeus sinensis by-products fermentation inoculated with Bacillus subtilis subsp. (PSB-Bs) for 7 days were evaluated. In addition, the flavor characteristics of PSB-Bs were determined by the combination of electronic nose (E-nose) and gas chromatography-ion mobility spectroscopy (GC-IMS). The results showed that the alkaline protease activity (pH 9) increased significantly in late fermentation stage (5–7 days), and the specific trypsin activity was also significantly higher than that of pepsin. E-nose and GC-IMS distinguished the variations of volatile compounds in PSB-Bs, and 67 volatiles were identified. Through orthogonal partial least squares discriminant analysis and random forest multivariate statistical analysis, 15 flavoring volatiles screened were further determined the correlation with protease activity. Negative relationships were found between the activity of protease (pH 7) or pepsin and pleasant flavors like 2, 5-dimethyl furan, hexyl acetate and styrene. Our results suggest that during fermentation, controlling the activities of pH7.0 protease and pepsin might help to improve the production or enrichment of pleasant flavor substances in PSB-Bs, which will help to enhance the acceptability and high-value utilization of shrimp by-products fermentation. Graphical abstract: Image 1 Highlights: Penaeus sinensis by-products inoculated with Bacillus subtilis subsp. for fermenting. Alkaline protease (pH 9) activity increased after 3 days of fermentation. 67 volatile compounds were identified by gas chromatography-ion mobility spectroscopy. Protease activity had high correlation with pleasant volatile compounds formation.